Variations in War Crimes During the Sierra Leone Civil War - Mullins, Christopher W. (International criminal justice review, 2023)
This article explores the nature of, and variation within, war crimes committed during the Sierra Leone civil war. Drawing upon testimonies given before the Sierra Leone Truth and Reconciliation Committee and from trials held by the Special Court for Sierra Leone, this article establishes that crimes were committed by all belligerents in the war. However, the type of crime, the frequency, and the motivation of crimes varied widely among the different armed forces. By contexting these acts within the aims, composition, and position of the various warring parties, this article discusses the role violations of the Geneva Conventions played in the short- and long-term goals of each army.